The total synthesis of (+)-paraherquamide B - Cushing, Timothy D., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1993)
The first stereocontrolled total synthesis of (+)-paraherquamide B is described in 42 chemical steps. The synthesis is a convergent one, starting from S-proline and vanillin. Vanillin was acylated, nitrated and hydrolyzed to supply o-nitrovanillin (131). This was converted to the azlactone, hydrolyzed to the α-ketocarboxylic acid, oxidatively decarboxylated and reductively cyclized to afford the oxindole 142. The oxindole was demethylated, regioselectively prenylated, epoxidized, and subjected to a key seven-membered ring forming procedure to provide the unique dioxepin 124. This ring forming methodology was explored in detail with two alternative procedures (epoxidation/SnCl4; PhSeCl, N-PSP) culminating in the synthesis of the dioxepins 148, 154, 188, 189, 192 , 195, 193, and 196. 124 was reduced, protected and subjected to a Mannich reaction to afford the gramine 220 in 4% overall yield. S-proline was condensed with pivaldehyde and allylated to give the key (Seebach) heterocycle, which was amidolyzed, cyclized, ozonolyzed and homologated to grant the (Williams) piperazinedione 91. This was oxidatively N-deprotected, reduced, O-silylated and dimethoxycarbonylated to afford the piperazinedione 271 in 20% yield from proline. This piperazinedione was alkylated with 220 to yield the indole 272, which was demethoxycarbonylated to provide two separable diastereomers 273 and 274. These were individually treated with Me3OBF4, (BOC)2O, and n-BU4NF to afford the diols 276 and 293. The allylic alcohols were converted to the chlorides, and resilylated to supply 290 and 295, which were subjected to a key regioselective SN2' cyclization. The resulting bicyclic piperazinedione 291 was cyclized, selectively reduced, N-methylated and deprotected to provide the indolepiperazinone 311. This indole-piperazinone 311 was oxidatively spiro-cyclized and dehydrated to afford (+)-paraherquamide B (3) in 1.4% yield from S-proline.
Keywords: Antibiotics -- Synthesis